Persepsi Mahasiswa Hukum Ekonomi Syariah (Hes) Terhadap Mata Kuliah Ekonomi Konvensional - Amilis Kina (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
To find out the perception of Islamic economics law students against conventional economics courses compared to Islamic economics courses, find out the relevance of both to the level of success and know the factors forming the perception of this conventional course. This type of quantitative research and in the form of secondary data that pour numbers, starting from data collection, interpretation of the data, and the appearance of the results. The population of this research is students of Islamic Economics Law IAIN Tulungagung. By presenting a sample of IAIN Tulungagung Islamic Economics Law majoring students taking conventional economics courses as many as 100 students were drawn from six sharia economics law classes. This research is based on qualitative data with quantitative data, we will present the data in graphical form then clarified with the description below. Respondents have positive perceptions about the importance of studying conventional economics and its relevance to increasing insight into the field of conventional economic scholarship. Respondents believe that conventional economics can help with certain legal issues. And conventional economics can create opportunities for ease and smoothness in undergoing a career later as law enforcement. Respondents proved to have a positive perception of conventional economic learning. This learning has benefits in getting good judgment. It was found that there are many factors that influence HES students in studying conventional economics. It can be seen that the important factor is the HR factor, namely the students themselves and the lecturer as the material deliverers. Motivation, students' perspectives and the insight of lecturers delivering the material are believed by the respondents as the main factors influencing their success in studying this conventional economic course. Factors that are considered to hinder the learning process of information systems in the HES department are as follows: Interest and motivation low for conventional economics learning; students' negative perceptions about the relevance of information systems to conventional economics.